Supremasi Kulit Putih di Balik Kemenangan Orang Kulit Hitam dalam Film Django Unchained (2012): Sebuah Kritik terhadap Ideologi Post-Racial di Amerika - R, Rendy Septiadi (UI Scholars Hub, 2015)
The writing examines how the process of maintaining the ideology of white supremacy and how Django’s character is constructed as a subject in planting white ideology in the movie Django Unchained (2012) based on the analysis of Django’s relationship with other characters. The appearance of the movie during the state of post-racial society in America can be seen as a form of criticism of the ideology, and the movie will be analyzed to deconstruct it. The approaches used in this thesis are Stuart Hall’s interpretation of Gramci’s hegemony in the context of racial. This study aims to look at the process of hegemony to maintain white supremacy and clarify the status of the controller and the controlled. Moreover, analysis of the characters’ relationship becomes important because Django’s relationship with the other white characters represent minority and majority group relations. With the results of this study, the movie Django Unchained is a medium to build and maintain the hegemony of white supremacy.